PENGARUH LITERASI PEMASARAN TERHADAP KEBERHASILAN PROYEK KEWIRAUSAHAAN - Wijaya, Michael Chandra; Arafah, Willy (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2024)
This research examines the impact of marketing literacy on the success of entrepreneurial projects. It identifies key factors such as customer service, management style, technology, and customer retention that significantly influence project outcomes. The study is grounded in existing literature that emphasizes the importance of marketing literacy in enhancing organizational understanding of market dynamics. Using a quantitative approach, data were collected through online questionnaires, targeting a diverse sample of respondents. The findings suggest that effective customer service and management practices contribute positively to entrepreneurial success, while technology adoption and customer retention strategies are critical in maintaining competitive advantage. This research aims to provide insights for future studies and practical implications for entrepreneurs seeking to improve project performance.